Ambarzumyan type theorem for a quadratic Sturm-Liouville operator - Koyunbakan, H.; Lesnic, D.; Panakhov, E. S. (My University, 2013)
We consider a quadratic Sturm-Liouville problem. In this paper, some uniqueness theorems are extended to the case in which the governing second-order ordinary differential equation contains both q(x) and p(x) instead of only q(x) . It is shown that if the spectrum is the same as the spectrum belonging to the zero potential, then the functions q(x) and p(x) are zero.

Bu çalışmada bir kuadratik Sturm-Liouville problemi ele alındı. Bazı teklik teoremleri, içerisinde sadece değil hem hemde bulunduran ikinci mertebeden adi diferensiyel denklem olması durumuna genişletildi. Spektrum eğer sıfır potansiyeline ait olan spektrum ile aynı ise, ve fonksiyonlarının sıfır olduğu gösterildi.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Quadratic Sturm-Liouville equation; Spectrum; Ambarzumyan's theorem MSC 2000: 34B24; Ambarzumyan's theorem MSC 2000: 34A55; Quadratik Sturm-Liouville denklemi; Spektrum; Ambarzumyan teoremi MSC 2000: 34B24; Ambarzumyan teoremi MSC 2000: 34A55